Effect of genistein addition to equine sperm freezing extender - MACÍAS-GARCÍA, Β.; GUIMARÃES, Τ.; LOPES, G.; ROCHA, A.; GONZÁLEZ-FERNÁNDEZ, L. (Journal of the Hellenic Veterinary Medical Society, 2018)
Cryopreservation negatively affects equine sperm quality post-thaw: an excessive release of reactive oxygen species (ROS) and increased protein tyrosine phosphorylation (known as cryocapacitation) have been demonstrated in frozenthawed equine sperm diminishing its lifespan. The objective of this study was to determine the possible beneficial effect of genistein addition (a ROS scavenger and protein tyrosine kinase inhibitor) to a commercial freezing extender. Equine sperm were frozen in the presence of different genistein concentrations ranging from 0 to 800 μM. After thawing, the sperm viability (eosinnigrosin), acrosome integrity using peanut agglutinin (PNA), protein tyrosine phosphorylation (PY) and motility were assessed at times 0 and 1 hr. In addition PY was studied in fresh and frozen sperm incubated in Modified Whitten’s (MW) medium with 25 mM Bicarbonate (MW+Bic). Genistein did not affect the viability, total or progressive motility or acrosome status of frozenthawed equine sperm. Immediately after thawing, positive PY staining in the equatorial band was observed and genistein addition did not exert any change in PY. Fresh sperm incubated in MW+Bic showed a significant increase in PY staining along the tail compared to frozen-thawed sperm. In our study sperm viability immediately post-thaw was 58.25% ± 5.35 and progressive motility 14.46% ± 5.7 (mean ± S.E.M.) and genistein did not improve the post-thaw quality of equine sperm. In addition, cryopreservation did not induce PY immediately post-thaw or enhanced frozen-thawed equine sperm susceptibility to PY induction.